High Photocurrent Gain of Spherical Nano-crystalline ZnO:Bi Film for Advanced Solar Cells Application - Peerawoot Rattanawichai (Science Faculty of Chiang Mai University, 2019)
Zinc oxide (ZnO) thin films are expected to have crucial applications in opto-electronic devices such as photo sensors, large-area displays and perovskite solar cells for an electron transport layer (ETL). In particular performance of nano-crystallinity for advanced photovoltaic (PV) cells, ZnO films have been very interested in recent years. However, their performances are not satisfactory at present: the photocurrent gain is quite low (<102 times more than dark current), the high reflectance R% is not beneficial to obtain high quality of PV cell, and the light-trapping enhancement on ZnO film has not yet been fully exploited in perovskite PV cells. Realizing high light-trapping and high photocurrent gain remain a big challenge today. In this paper, nano-crystalline zinc oxide films doped with bismuth (nc-ZnO:Bi) were synthesized through sol-gel processing and then formed by spin coating method. By adding the cation surfactant as cetyl trimathylammonium bromide (CTAB) in the sol-gel, good film quality and spherical nano-ZnO:Bi were obtained and performed at temperature annealing between 350-550C. Reflectance as low as 17% and transmittance (%T) of over 90% in the light wavelength between 390-800 nm, photoresponsivity values of 8 -28 A/mW and high photocurrent gain as high as 1ด104 times comparing with dark current were achieved. The surface morphology of ZnO:Bi films with existence of spherical nano-particles with diameter size around 10-20 nm acts as light-trapping surface to improve photocurrent enhancement. Moreover, such high quality of their optical properties is able to contribute light-trapping performance of ETL for further emerging solar cells.